2014
DOI: 10.1073/pnas.1411216111
|View full text |Cite
|
Sign up to set email alerts
|

Ultradian corticosterone pulses balance glutamatergic transmission and synaptic plasticity

Abstract: The rodent adrenal hormone corticosterone (CORT) reaches the brain in hourly ultradian pulses, with a steep rise in amplitude before awakening. The impact of a single CORT pulse on glutamatergic transmission is well documented, but it remains poorly understood how consecutive pulses impact on glutamate receptor trafficking and synaptic plasticity. By using high-resolution imaging and electrophysiological approaches, we report that a single pulse of CORT to hippocampal networks causes synaptic enrichment of glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 27 publications
5
55
0
1
Order By: Relevance
“…The rapid effect does not require protein synthesis and involves a receptor that is localised close to the plasma membrane because BSA-linked corticosterone was active outside but not inside the cell. In hippocampal CA1 neurons, this receptor seems to be located both presynaptically, linked to the ERK1/2 signalling pathway, and post-synaptically, involving G-protein signalling (Karst et al 2005, Olijslagers et al 2008, Sarabdjitsingh et al 2014.…”
Section: Non-genomic Mr-mediated Actionsmentioning
confidence: 99%
“…The rapid effect does not require protein synthesis and involves a receptor that is localised close to the plasma membrane because BSA-linked corticosterone was active outside but not inside the cell. In hippocampal CA1 neurons, this receptor seems to be located both presynaptically, linked to the ERK1/2 signalling pathway, and post-synaptically, involving G-protein signalling (Karst et al 2005, Olijslagers et al 2008, Sarabdjitsingh et al 2014.…”
Section: Non-genomic Mr-mediated Actionsmentioning
confidence: 99%
“…These circadian changes in cortisol concentration are likely to affect many important homeostatic processes in the body, including the balance between neuronal excitability and inhibition [12][13][14]. However, the relationship between circadian fluctuations in cortisol levels and seizure susceptibility is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that the pattern of GCs pulses differentially regulates glutamatergic neurotransmission and long-term potentiation (LTP, an important neuronal mechanism considered to underlie memory formation) induction in cultures of hippocampal neurons and dorsal hippocampal slices from rodent brains (Sarabdjitsingh et al, 2014), while a previous study has described the phenomenon of gene pulsing in rat hippocampus following pulses of GCs (Conway-Campbell et al, 2010).…”
Section: How Is Gc Rhythmicity Biologically Perceived By the Brain?mentioning
confidence: 99%